Congenital adenohypophyseal hypoplasia associated with secondary hypothyroidism in a 2-week-old Portuguese water dog - Gal, Arnon (Canadian Veterinary Medical Association, 2012)
This report describes the histomorphological changes of central hypothyroidism (pituitary dependent) in several target organs of thyroid hormones of a Portuguese water dog, and contrasts those with the reported features of central hypothyroidism in German shepherd dogs, in which central hypothyroidism is a part of a combined pituitary hormonal deficiency.